Проблеми водопостачання півдня Донецької області - Калашник, Л.П.; Фощій, М.В. (Наукові праці УкрНДМІ НАН України, 2011)
Обеспечение юга Украины питьевой водой, в том числе и юга Донецкой области, является проблемой актуальной. На водозаборах подземных вод, которые подают воду потребителю централизовано, вода не соответствует требованиям ДСанПіН 2.2.4-171-10 "Гігієнічні вимоги до води питної, призначеної для споживання людиною" и ГОСТ 2874-82 «Вода питьевая». Providing the south of Ukraine including also south of the Donetsk region with drinking water is a pressing problem. At ground water intakes, which pump water online to the customer, water does not meet the requirements of public health regulations ДСанПіН 2.2.4-171-10 “Hygiene requirements to drinking water aimed at human consumption” and National Standard ГОСТ 2874-82 “Drinking water”.